Landing-Takeoff Asymmetries Applied to Running Mechanics: A New Perspective for Performance - da Rosa, Rodrigo Gomes; Oliveira, Henrique Bianchi; Gomeñuka, Natalia Andrea; Masiero, Marcos Paulo Bienert; da Silva, Edson Soares; Zanardi, Ana Paula Janner; de Carvalho, Alberito Rodrigo; Schons, Pedro; Peyré-Tartaruga, Leonardo Alexandre (Frontiers in Physiology, 2019)
Background: Elastic bouncing is a physio-mechanical model that can elucidate running behavior in different situations, including landing and takeoff patterns and the characteristics of the muscle-tendon units during stretch and recoil in running. An increase in running speed improves the body’s elastic mechanisms. Although some measures of elastic bouncing are usually carried out, a general description of the elastic mechanism has not been explored in running performance. This study aimed to compare elastic bouncing parameters between the higher- and lower-performing athletes in a 3000m test. Methods: Thirty-eight endurance runners were divided into two groups based on 3000m performance: the high-performance group (Phigh; n=19; age: 29±5 years; mass: 72.6±9.9 kg; stature: 177±8 cm; 3000time: 682±56 s) and the low-performance group (Plow; n=19; age: 29±5 years; mass: 74.3±7.5 kg; stature: 177±8 cm; 3000time: 765±45 s). They performed three tests on different days: i) 3000m on a track; ii) incremental running test; and iii) a running biomechanical test on a treadmill at 13 different speeds from 8 to 20 km h-1. Performance was evaluated at 3000m, and biomechanics variables included effective contact time (tce), aerial time (tae), positive work time (tpush), negative work time (tbreak), step frequency (fstep) and elastic system frequency (fsist), vertical displacement (Sv) in tce and tae (Sce and Sae), vertical force (Fv), and vertical stiffness (kvert.). Results: The tae, fsist, kvert and Fv were higher (p<0.05) and tce and fstep were lower (p<0.05) in Phigh, with no differences between groups in tpush and tbreak. Conclusion: The elastic bouncing was optimized in runners of the best performance level, demonstrating a better use of elastic components.